2019
DOI: 10.1007/s12551-019-00513-6
|View full text |Cite
|
Sign up to set email alerts
|

Advances in domain and subunit localization technology for electron microscopy

Abstract: The award of the 2017 Nobel Prize in chemistry, 'for developing cryo-electron microscopy for the high-resolution structure determination of biomolecules in solution', was recognition that this method, and electron microscopy more generally, represent powerful techniques in the scientific armamentarium for atomic level structural assessment. Technical advances in equipment, software, and sample preparation, have allowed for high-resolution structural determination of a range of complex biological machinery such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…This protocol revealed that 131 I-PEG-AuNRs are extraordinary stable in vivo condition. In a recent work, cyclic arginine-glycine-aspartate acid (RGD)-conjugated gold nanoparticles were used to follow integrins in high resolution by means of cryo-electron tomography: it is possible to localize AuNPs in cells and identify the precise interactors within cells [115,116]. This development is a clear example of the AuNPs use of structural cell biology.…”
Section: Aunrsmentioning
confidence: 99%
“…This protocol revealed that 131 I-PEG-AuNRs are extraordinary stable in vivo condition. In a recent work, cyclic arginine-glycine-aspartate acid (RGD)-conjugated gold nanoparticles were used to follow integrins in high resolution by means of cryo-electron tomography: it is possible to localize AuNPs in cells and identify the precise interactors within cells [115,116]. This development is a clear example of the AuNPs use of structural cell biology.…”
Section: Aunrsmentioning
confidence: 99%